STAD compare to GTM. Hopefully, this method can cover the students need in reading comprehension - Kurnia Devi Yuswandari (Mastery: Master of English Language Journal, 2022)
The main objectives of the research are to find out: (1) whether STAD method is more effective than grammar-translation method to teach reading; (2) whether the students who have high verbal intelligence have better reading mastery than those who have low verbal intelligence; and (3) whether there is an interaction between teaching methods and students’ verbal intelligence. Kind of this research was experimental research. This research was carried out at SMAN 3 Lumajang in the academic year of 2014/2015. The population of the research is the eleventh grade student of SMAN 3 Lumajang in the academic year of 2014/2015. The samples were two classes. In taking the sample, cluster random sampling technique was used. Each class was divided into two groups (the students who have high and low verbal intelligence). Then, the techniques which were used to collect the data were verbal intelligence test and reading test. The two instruments were tried out to get valid and reliable items. The data were analyzed by using multifactor analysis of ANOVA 2x2 and Tuckey test. Based on the results of the analysis, there are some research findings that can be taken: (1) STAD method is significantly different from GTM method to teach reading because Fo is higher than Ft and qo between columns (C1 and C2) is higher than qt. STAD method is more effective than GTM to teach reading because the mean of C1 is higher than C2; (2) the reading mastery of the students who have high verbal intelligence is significantly different from that of those who have low verbal intelligence because Fo is higher than Ft and qo between rows (R1 and R2) is higher than qt and the students who have high verbal intelligence have better reading mastery than those who have low verbal intelligence because the mean of R1 is higher R2; and (3) there is an interaction between teaching methods and verbal intelligence for teaching reading because Fo is higher than Ft: (a) for the students who have high verbal intelligence, STAD method is significantly different from GTM method to teach reading because qo between cells (A1B1 and A2B1) is higher than qt . STAD method is more effective than GTM method to teach reading because the mean A1B1 is higher than A2B1, and (b) for the students who have low verbal intelligence, GTM method is significantly different from STAD method to teach reading because qo between cells (A2B2 and A1B2) is higher than qt and GTM method is more effective than STAD method to teach reading because the mean of A2B2 is higher than A1B2. The research finding are: (1) STAD is more effective than GTM for teaching reading; (2) The students having high verbal intelligence have better reading mastery than the students having low verbal intelligence; (3) There is an interaction effect between methods and students’ verbal intelligence for teaching reading. STAD is suitable for students having high verbal intelligence and GTM is suitable for students having low verbal intelligence. It is important for English teacher to select the method which is suitable for students who have high or low verbal intelligence in English lesson.